Teachers in Rural Primary Schools: A Study of Their Perceptions on Teacher Preparation, School Environment and Parental Involvement - Abdul Rahman, Azizah; Md. Nor, Sharifah; Mokhtar, Halimatun Halaliah; Halimi, Faridah (Universiti Putra Malaysia Press, 1993)
This paper discusses the findings of a study which was carried out on 287 primary teachers and 24 principals in a rural Malaysian district. The aim was to construct a profile of the teachers, their perception of school facilities, slUdents, parents, principals and the adequacy of teacher training. Interviews were con!iucted and questionnaires administered. The data show that generally teachers are satisfied with the basic facilities in their schools; they find their work challenging and they are committed to serve rural communities. However, they are constrained by lack of parental involvement, low motivation among pupils, inadequate. residential facilities and teaching aids. They perceive their teacher preparation as generally adequate, but indicate that more need to be done in terms of a longer preservice exposure in rural areas, teaching methods and subjects tailored to rural needs, skills in producing teaching aids and carrying out suitable co-curricular activities. However, they agree that guidance and support given in schools are more important than college preparation. The paper concludes with a discussion on the implications for teacher education (preservice and inservice) and school support for teachers.